The difference among structure, physicochemical and functional properties of dietary fiber extracted from triticale and hull-less barley. (15th January 2022) - Xiong, Min; Zheng, Siyuan; Bai, Tingmei; Chen, Daiwen; Qin, Wen; Zhang, Qing; Lin, Derong; Liu, Yuntao; Liu, Aiping; Huang, Zhiqing; Chen, Hong
Abstract: The dietary fiber (DF) composition, physicochemical and functional properties of triticale dietary fiber (TRDF ) and hull-less barley dietary fiber (HUDF ) were investigated and compared in this study. Results revealed that triticale soluble dietary fiber (TRSDF ) had higher arabinose and xylose contents but lower glucose content than that of hull-less barley soluble dietary fiber (HUSDF ). Compared with hull-less barley insoluble dietary fiber (HUIDF ), triticale insoluble dietary fiber (TRIDF ) had more arabinose and xylose. HUSDF exhibited a smaller particle size and lower viscosity than TRSDF . HUSDF had greater hydroxyl scavenging activity, whereas TRSDF showed higher DPPH radicals scavenging activity. Glucose adsorption capacity, glucose dialysis retardation index, and α-amylase and α-glucosidase inhibitory activities of TRSDF were all higher than those of HUSDF . TRIDF and its bound polyphenols demonstrated higher α-amylase and α-glucosidase inhibitory activities than those of HUIDF and its polyphenols. In conclusion, TRDF had better hypoglycemic activities than that of HUDF and the antioxidant activity of TRIDF was lower than that of HUIDF . Highlights: FT-IR spectra of triticale and hull-less soluble dietary fiber were different. Bound polyphenols contributed to the antioxidant capacity of two dietary fibers. Triticale soluble dietary fiber showed higher hypoglycemic properties. Triticale soluble dietary fiber had larger particle size and higher viscosity. Triticale insoluble dietary fiber showed lower antioxidant properties.